Routine cavity shaves following breast conserving surgery; friend or foe?. (June 2021) - Monib, Sherif; Anis, Karim; Habashy, Hany
Abstract: Background: Radial margin status is considered one of the most important prognostic predictor for patients undergoing breast-conserving surgery (BCT), not only related to regional recurrence but also to 5y survival, especially in patients with invasive disease. Aim: While our primary aim was to evaluate whether doing routine radial cavity shaves following at the time of primary conservative breast surgery will decrease the need for a second operation or not, our secondary aim was to assess time added to the operation to resect and mark the radial shaves, as well as patients' satisfaction with the results. Material and methods: We have conducted a case series prospective analysis, including158 patients who underwent breast-conserving surgery looking into the histological status of resection margins and radial shaves, added time taken to take and mark the shaves as well as patients' satisfaction. Results: 158 female breast cancer patients have been included in our analysis, the mean age was 56 years; total number of lesions was 160. While 89.3% of lesions were palpable, 10.6% were not requiring wire-guided localisation. Mean tumour size was 24 mm SD 7, final histology revealed that 86.8% lesion was invasive ductal carcinoma, 5.6% invasive lobular carcinoma, 1.2% medullary carcinoma. 12.4% had invasive disease as well as DCIS, and 1.8% had DCIS only with no invasive disease. Mean preoperative breast volume was 723 ml, Mean wide local excision specimen weight was 73 g, and mean shave weight was 1.6 g. Total number of radial margins was 640, 81.8% was clear, 14.6% was close, and 3.4% was involved. Total number of shaves was 640 out of which 98.7% was clear 0.7% was close and 0.4% was involved. Out of the 160 lesions, 3.7% required a second procedure to clear margins, out of which 2.5% had re-excision for close or involved single shaves each while 1.2% had mastectomy due to close or involved two shaves each. Average time utilised in resection of radial shaves and marking was 7 min 0.6% of patients developed a haematoma, 1.8% had a Seroma, and 1.2% had wound infection. Mean hospital stay was 1day SD 1. Conclusion: Routine radial cavity shaves not only ensure microscopic clearance, reduce the need for re‐excision with no significant added operating time but also has no impact on patients' satisfaction. Highlights: Routine radial cavity shaves is a reliable technique in achieving clear margins. Routine radial cavity shaves have minimal impact on operating time. Routine radial cavity shaves it was associated with better patient satisfaction. Routine radial cavity shaves provide adequate well-oriented material for assessment.